SOME SOCIO-CULTURAL AND ECONOMIC FACTORS BEHIND THE PHENOMENON OF DIVORCE IN ALGERIA. A FIELD STUDY IN THE WILAYA OF M’SILA - Salim Mahmoudi; Fatiha Hank; Hanan Messouaka; Abdelhakim Karrouche (International Journal of Innovative Technologies in Social Science, 2025)
This study aimed to investigate the economic and socio-cultural factors contributing to the phenomenon of divorce. Divorce has recently garnered significant attention from researchers and those interested in family issues, especially as Algerian society has witnessed a noticeable rise in various social phenomena, including divorce. Although divorce results in the dissolution of the marital relationship, it is closely linked to several contributing factors that have fueled its spread. The study revealed findings that confirm the role of certain economic and socio-cultural factors in the occurrence of divorce. Among the key indicators identified were: the rising educational level of women, their entry into the labor market, financial independence, freedom in decision-making, the husband’s unemployment, and interference from extended family members.